INDIVIDUAL PATTERN APPROACH THE IMPROVEMENT OF LEARNING OUTCOMES IN THE PASSING ATAS IN VOLLEYBALL IN CLASS VIII SMP INDUSTRIAL CIAMPEL - DIDIK FAUZI DERMAWAN (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2016)
The purpose of this research was to determine the patterns of individual approach to learning outcome overhead passing in volleyball. Whether there is influence patterns of individual approach to the learning outcomes overhead passing in volleyball? This research using quantitative approach, the experimental research methods. sample in this research 30 students with simple random sampling. Research instruments to test overhead passing in volleyball. Based on research results there are significant individual pattern approach to learning outcome overhead passing in volleyball in class SMP VIII Industri Ciampel. Kata kunci : Learning, individual approach, Overhead passing, volleyball